Virtual commander’s operational decision-making model based on thinking simulation - JIA Chenxing, MING Yuewei, GE Chenglong (Zhihui kongzhi yu fangzhen)
Focusing on the urgent need of joint operational plan simulation experimentation, aiming at the lack of intelligent decision-making ability of command entity in the current joint operations simulation systems, and the difficulty of popularizing the simulation experimentation pattern of man-not-in-loop, this paper researches a joint campaign level simulation intelligence which named virtual commander in the simulation loop to simulate the thinking and behavior of human commander’s operation decision-making. This paper puts forward the definition and orientation of virtual commander’s operational decision-making, constructs a framework of virtual commander’s operational decision-making model, and designs the virtual commander’s operational decision-making thinking model, behavior model and simulation model based on the theory of natural decision-making, which provides a feasible solution to the bottleneck problem of simulation experimentation pattern of Man-Not-In-Loop.